Environmental Justice and Human Rights on the Mining Wastelands of the Witwatersrand Gold Fields - Humby, Tracy-Lynn (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2013)
In South Africa, the constitutional and statutory framework seemingly establishes a strong synergy between environmental rights and environmental justice. A prevailing notion of transformative constitutionalism additionally positions law as the foundation for large-scale social change through non-violent political processes. A case study of the Tudor Shaft Informal settlement on the Witwatersrand goldfields elucidates the ambiguities in the notion of environmental justice and the tensions between claims based on the environmental right and socio-economic rights. By highlighting the existence of local moral orders—political alliances based on access to resources that frequently employ violence to achieve political ends—it also suggests the limited reach of the constitutional order and the project of transformative constitutionalism.